Mszaki rezerwatu „Jamno” - Wolski, Grzegorz J.; Woziwoda, Beata; Pawicka, Katarzyna (Biuletyn Szadkowski, 2012)
The 39 bryophytes species – seven liverworts and 32 mosses belonged to 21 families have been noted in “Jamno” nature reserve in 2011. “Hypnaceae, Brachytheciaceae” and “Dicranaceae” are families represented by the highest number of species (see table 1). Bryophytes grow on various type of habitat: epigeic – mineral soil, humus and litter, epiphytic – bark of trees, epixylic – tree stumps and epilithic – stones. The highest number of mosses was found on bark of silver firs Abies alba, pedunculate oaks “Quercus robur”, silver birches “Betula pendula” and Scots pines “Pinus sylvestris”. Five valuable protected species “Dicranum scoparium”, “Leucobryum glaucum”, “Pleurozium schreberi”, “Pseudoscleropodium purum” and “Thuidium tamariscinum” were noted in this small forest reserve. The occurrence of one mountain species “Hypnum pallescens” is also interesting and noteworthy.